2012
DOI: 10.1111/j.1466-8238.2012.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elevated UVB radiation on marine biota: a meta‐analysis

Abstract: Aim The emission of chlorofluorocarbon compounds eroded the ozone layer, raising incident ultraviolet B radiation to levels that affect biota. However, the role of UVB radiation (280–315 nm), which remains elevated to date, as a possible driver of the widespread global deterioration of marine ecosystems has not yet been fully quantified. In this paper we assess the magnitude of the impacts of elevated UVB radiation and evaluate the relative sensitivity to UVB across marine taxa and processes. Location The anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 56 publications
3
111
0
1
Order By: Relevance
“…Nonetheless, as both a warming of the Southern Ocean and the positive SAM phase shift are predicted to continue as long as the ozone hole remains open and greenhouse gas emissions continue to increase [59][60][61], it can be reasonably expected that there will be ongoing changes in the structure and function of the Southern Ocean ecosystem. Such changes are likely to further affect productivity of the polar marine ecosystem [62] and mid-to high-order predator populations, some of whom will prosper while others struggle.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as both a warming of the Southern Ocean and the positive SAM phase shift are predicted to continue as long as the ozone hole remains open and greenhouse gas emissions continue to increase [59][60][61], it can be reasonably expected that there will be ongoing changes in the structure and function of the Southern Ocean ecosystem. Such changes are likely to further affect productivity of the polar marine ecosystem [62] and mid-to high-order predator populations, some of whom will prosper while others struggle.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focused on micro-and macro-algae due to their comparable and relatively large datasets, as data on responses of aquatic angiosperms are sparse. The resulting dataset of marine photosynthetic organisms included previous compilations [Agustí et al (2015) and Llabrés et al (2013), microalgae: n = 454, macroalgae: n = 432] and additional data published from April 2013 to July 2015 (microalgae: n = 633, macroalgae: n = 461) by a search on Web of Science and Google Scholar for the relevant keywords: UV radiation, aquatic and marine. Agustí et al (2015) and Llabrés et al (2013) reported data only for marine photosynthetic organisms, so the dataset on freshwater photosynthetic organisms, was produced entirely from reports retrieved from searches in the Web of Science and Google Scholar from 1950s to July 2015.…”
Section: Data Selectionmentioning
confidence: 99%
“…Photosynthetic organisms are more resistant than non-photosynthetic organisms to UVB (Llabrés et al, 2013;Agustí et al, 2015), suggesting that photoprotective and reparatory systems designed to counter UVB exposure operate efficiently in photosynthetic organisms. However, UVB radiation causes negative effects on the photosynthetic performance of micro-and macro-algae by reducing their photosystem II efficiency (e.g., Jiang and Qiu, 2005;Jin et al, 2013;Zhang et al, 2013), electron transport rate (e.g., Figueroa et al, 2014;Zhu et al, 2015) as well as photosynthetic carbon fixation rate (e.g., Villafañe et al, 2007;Helbling et al, 2008;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar radiation reaching the surface of the water column includes visible light (PAR, wavelengths between 400 and 700 nm) and ultraviolet radiation (UVR, 280-400 nm) which in turn comprises ultraviolet A (UVA, 315-400 nm) and ultraviolet B (UVB, 280-315 nm) radiation. In general, UVR has detrimental effects on plankton (Gonçalves et al, 2010;Llabrés et al, 2013) and several species are able to detect and avoid high-UVR surface waters (Speekmann et al, 2000;Richter et al, 2007a;Cohen & Forward Jr., 2009). An exposure of a few hours under UV radiation may produce negative effects on crab larvae (Morgan & Christy, 1996;Hovel & Morgan, 1999;Hernández-Moresino & Helbling, 2010;Hernández-Moresino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%